2021
DOI: 10.1177/1078155220981150
|View full text |Cite
|
Sign up to set email alerts
|

MDR1 gene polymorphisms and imatinib response in chronic myeloid leukemia: A meta-analysis

Abstract: Background Our study aimed to investigate the association between multidrug resistance (MDR1) C1236T, C3435T and G2677T/A polymorphisms and the response to imatinib (IM) in chronic myeloid leukemia (CML). Materials and methods An electronic databases in PubMed, Embase, Web of Knowledge, Scopus and Cochrane were searched using combinations of keywords relating to MDR1 polymorphisms and the response to IM in CML. Studies retrieved from database searches were screened using strict inclusion and exclusion criteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
(54 reference statements)
0
5
0
Order By: Relevance
“…TKI efficacy is highly dependent on cellular drug concentration to effectively block BCR-ABL activity, and low TKI concentrations have already been associated, at least in part, with reduced expression or activity of SLC transporters and/or increased expression or activity of ABC transporters [ 40 , 41 ]. The SNVs studied here, which are associated with altered expression and activity, have a potential role in response to therapy [ 42 , 43 ]. Recently Rajamani et al showed the influences of ABCB1 polymorphisms and plasma imatinib levels on early molecular response and failure-free survival [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…TKI efficacy is highly dependent on cellular drug concentration to effectively block BCR-ABL activity, and low TKI concentrations have already been associated, at least in part, with reduced expression or activity of SLC transporters and/or increased expression or activity of ABC transporters [ 40 , 41 ]. The SNVs studied here, which are associated with altered expression and activity, have a potential role in response to therapy [ 42 , 43 ]. Recently Rajamani et al showed the influences of ABCB1 polymorphisms and plasma imatinib levels on early molecular response and failure-free survival [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The association between of the MDR1 gene (C1236T, G2677T/A, and C3435T SNPs) and IM resistance acquisition in CML patients was extensively studied and meta-analyzed [14] [25] [26]. A recent meta-analysis (2021) concluded that MDR1 SNPs genotypes are not significantly related to the IM response in patients with CML [26], which is contrary to some previous studies that showed genetic variations were associated with the increasing risk of resistance to IM in CML patients [17] [24]. These heterogeneous results illustrate a potential role of ethnicity in the genetic context [32].…”
Section: Discussionmentioning
confidence: 99%
“…MDR1 is a highly polymorphic gene with at least 50 SNPs. Some of these SNPs have been extensively studied in CML disease: two silent SNPs C1236T (rs1128503), and C3435T (rs1045642) in the exon 12 and 26, respectively; and one missense SNP G2677T/A (rs2032582) located in exon 21 [14] [16]- [26]. However, although various attempts to explain the impact of the MDR1 variants on IM efficacy in patients with CML, the outcomes remain contradictor rather than conclusive.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic myeloid leukemia (CML) is a multifactorial clonal myeloid neoplasm originating from malignant hematopoietic stem cells [1][2][3] with an approximate incidence of one to two per 100,000 adults worldwide [4]. The reciprocal translocation (t (9; 22) (q34; q11)) resulting in the Philadelphia (Ph) chromosome formation is pivotal to the pathogenesis of CML [8].…”
Section: Introductionmentioning
confidence: 99%